Older women's well-being during the COVID-19 pandemic: individual, community, and contextual factors - Banda, Andrew; Hoffman, Jaco; Roos, Vera (Frontiers in Global Women's Health, 2024)
ObjectiveThis article aims to examine the influence of individual and community-contextual factors on the well-being of older women in Zambia during the COVID-19 pandemic, drawing on Bronfenbrenner's process-person-context-time model.MethodsSecondary data from the nationally representative 2021 SEIA were used, and bivariate and logistic regression analyses were performed to determine factors associated with the well-being of older women during the COVID-19 pandemic.ResultsOverall, 29% (613) of older women reported a decline in their well-being due to COVID-19. Older women in rural areas had lower odds of well-being [Adjusted Odds Ratio (AOR) 0.607, 95% 0455,0.809]. At the individual level, the well-being of older women during COVID-19 was associated with age (AOR O.362, 95% CI: 0.190,0.689) and being in paid work (AOR 0.737, 95% CI: 0.552,0.984). Despite education having a strong relationship with well-being, it had a weak effect on the well-being of older women during COVID-19. Community-level factors significantly associated with the well-being of older women amidst COVID-19 included attendance at public gatherings (e.g., church meetings, funerals) (AOR 1.465, 95% CI: 1.139,1.885) and perceived fear or anxiety due to COVID-19 (AOR 0.522, 95% CI: 0.392,0.696). A significant contextual-level factor was access to transport services during the pandemic (AOR 0.589, 95% CI: 0.390,0.890).ConclusionCOVID-19 has exposed the inadequacy of systems at different levels in meeting the needs of older women and promoting their well-being during emergencies. At the individual level, there is a need to support older women's livelihoods and educational opportunities. Despite limitations on social interactions during COVID-19, access to social gatherings and interactions supported older women's well-being. However, this was hampered by fear of contracting COVID-19 and the limitations in public transport that compromised their mobility to access services and visit people. A more extensive analysis of individual, community, and contextual factors should identify factors that support or compromise the well-being of older women during emergencies or shocks. There is a need for information about what livelihood strategies during and/or post shocks, or critical events such as COVID-19 could sustainably support older women's well-being.